2010
DOI: 10.1016/j.juro.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Hypocitraturia and Hyperoxaluria After Roux-en-Y Gastric Bypass Surgery

Abstract: Purpose Roux-en-Y gastric bypass surgery is associated with an increased risk of nephrolithiasis but obesity itself is a known risk factor for kidney stones. To assess the mechanism(s) predisposing to nephrolithiasis after Roux-en-Y gastric bypass we compared urinary tract stone risk profiles in patients who underwent the procedure and normal obese individuals. Materials and Methods In this cross-sectional study urine and serum biochemistry was evaluated in 19 nonstone forming patients after Roux-en-Y gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 31 publications
5
31
1
3
Order By: Relevance
“…Indeed, 47% of RYGB patients manifest hyperoxaluria compared to just 10.5% in obese controls, predisposing this population to the development of calcium oxalate type stones. 13 Calcium and vitamin D supplementation are routinely prescribed post-RYGB to prevent urolithiasis by decreasing oxalate absorption from the digestive tract. However, previous studies have shown that compliance with nutritional supplementation and vitamin D is only 33 and 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 47% of RYGB patients manifest hyperoxaluria compared to just 10.5% in obese controls, predisposing this population to the development of calcium oxalate type stones. 13 Calcium and vitamin D supplementation are routinely prescribed post-RYGB to prevent urolithiasis by decreasing oxalate absorption from the digestive tract. However, previous studies have shown that compliance with nutritional supplementation and vitamin D is only 33 and 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some detailed analyses of the hyperoxaluria occurring after bariatric surgery have been performed by measuring urinary oxalate excretion in 24-h urine collections [9][10][11][12][13][14][15][16]. Duffey et al [10,11] conducted a long-term prospective study of the hyperoxaluria after R-Y gastric bypass, and revealed that the postoperative mean urinary oxalate excretion was significantly elevated from baseline at 3 months, and continued to grow in magnitude, reaching a stable level 1-2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggest that modern bariatric procedures, such as Roux-en-Y bypass, may also impart a twofold increased risk of nephrolithiasis, while 20-75% may have hyperoxaluria, including 20% with very high urine oxalate levels, also putting them at considerable risk of oxalate nephropathy (Table 2) (2,(5)(6)(7)(8)(9)(10)(11)(12). Purely restrictive bariatric procedures, such as gastric banding, may not increase oxalate excretion, yet more data are needed (Table 2) (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%